Learning with the urban form of (in)formal Maputo - Leite dos Santos Viana, David Manuel (2013)
This paper focuses on the urban form of Maputo. It draws not only on physical results, but also on the description of the process of structuring and transformation of the urban form. The main purpose of the paper is to understand a set of complex morphological relations that have been developed based on the dichotomy between the ‘concrete city’ and the so-called cidade caniço. The methodolody, supported on a case study, involved field survey, graphic representation, photographic survey, exploratory interviews and different data collection. Data processing, redesign and comparative analysis of multiple morphological elements of the city of Maputo were developed to obtain a spatially and chronologically ordered set of data. Morphological methods were applied to describe and explain the main characteristics of the urban transformation of the capital of Mozambique. This paper rejects the dual perspectives on the urban form of Maputo. On the contrary, it sustains that informal processes should be part of a number of principles for inclusive intervention on the city. The purpose is not to obtain a synthesis between the ‘concrete city’ and the cidade caniço, expressing the intricate contrasts of the urban form of Maputo, but to recognize the need for a wider morphological framework.